Investigação do potencial antimicrobiano de Casearia sylvestris sobre microrganismo endossimbionte de Diabrotica speciosa - Marques, Fabiana Aparecida (2013)
Diabrotica speciosa is a pest insect which occurs in most Brazilian states, standing out as one of the most important polyphagous pest of in grain crops. The understand of the role of the microbiota present in the digestive tract and of this insect the identification of ways to interfer or even to eliminate this microbial flora they are knowlegdes that, may lead mode of action to control of the pest insect. In this context, this study aimed to evaluate the microbial diversity present in the digestive tract of larvae and adults of D. speciosa and in the sometime, to investigate the potential of C. sylvestris as an antimicrobial agent. As results, they were obtained 21 bacterial isolates and 8 fungal isolates. The proteic profile of these microrganisms were analyzed by using MALDI-TOF/MS. Afterwards, these data were grouped identifying clusters of isolates. A bacteria each groups was identified by rDNA sequencing, 16S region. Identified bacteria were: Pantoea agglomerans, Luteibacter sp., Serratia marcescens, and Pseudomonas temperans Acidovorax sp. Two isolated fungi were identified through morphological comparison with literature data, and identified as Cladosporium sp. and Penicillium sp. A further study was carried out with Luteibacter sp bacteria, which were isolated from D. speciosa larva. In this study was evaluated growth profile and the parameters to carry out the antimicrobial assay. Several kind of microbial assays were investigated such as agar diffusion and microdilution plate ELISA®. The second method showed the best results. Thus, a microdiluition methodology using fluorometric assay, was developed and validated, highlighting parameter such as linearity, specificity, accuracy, precision, robustness, recovery, limites of detection, quantification and detection, etc. This method was applied evaluating extracts, fraction and secondary molecules of cerrado plants. Phytochemical study of C. sylvestris leaves resulted in the isolation of an umpublished tricyclic sesquiterpene, the flavonoid catechin and a clerodane diterpene, which was used as a reference marker in chromatographic method to quality control of the extracts and fractions of C. sylvestris that were used in assays.